Muslim Diaspora in the West : Negotiating Gender, Home and Belonging. - Moghissi, Haideh; Ghorashi, Halleh (Research in migration and ethnic relations series., 2010)
In view of the growing influence of religion in public life, Muslim Diaspora in the West offers a timely contribution to scholarly debates and concerns raised in the West about Islam and Muslims within diaspora. Presenting the latest research from a variety of locations on both sides of The Atlantic, this volume will be of interest to scholars with interests in race and ethnicity, cultural, media and gender studies, and migration.